The Efficacy of a Caudal Bupivacaine and Bupivacaine-Tramadol Combination for Postoperative Analgesia in Pediatric Lower Abdominal Surgeries - Ahmed Uddin Soomro, Imran Ali, Zaheer Ahmed, Khawar Aziz, Kelash Kumar, Imran Hafeez, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The major responsibility of perioperative pediatric anesthesia is to control acute pain in children undergoing surgery. Because some analgesics have synergistic or additive effects, they can be used to create balanced analgesia. This method of pain treatment is widely employed. Caudal analgesia is the most appropriate and tolerable type of postoperative analgesia for small children undergoing anoperineal, inguinal, or urogenital surgery. Objective: To evaluate the duration of analgesia in two comparison groups where one group is given bupivacaine only and the other group tramadol is given tramadol in addition to bupivacaine. Study Design: A Randomized Control Trial Place and Duration: This study was conducted in CMC Hospital @ SMBBMU Larkana from March 2022 to March 2023 Methodology: A total of 110 patients undergoing lower abdominal surgery were inducted into the study, with 955 in each group using a simple random sampling method. The lottery approach was used to randomly assign 55–55 patients to each group. Patients in Group A received 90.59 mL/kg 0.25%, while patients in Group B received 0.5 mL/kg of bupivacaine 0.25% with tramadol 2 mg/kg. We analyzed the data using SPSS version 23. Results: The mean age and mean weights were 4.83 ± 1.87 and 11.31 ± 3.88 in group A and 5.16 ± 1.9 and 12.46 ± 3.77 in group B. There were 38 (69.09%) males in group A and 42 (76.36%) males in Group B. Most (58.18%) of the children were aged 2 to 6 years in group A; similarly, in group B, most (52.73%) of the children were in the same age group. The mean duration of the analgesia in all three age groups in Group A was significantly higher than all the children in Group B, with a p-value of less than 0.005. Conclusion: It is concluded that for post-operative patients who went through lower abdominal surgeries, the use of tramadol along with bupivacaine for analgesia yields sustained analgesia and is completely safe for the young and elderly patients. Keywords: Bupivacaine, Tramadol, Abdominal Surgery, Pain